إبن رشد: حياته وأعماله وآرائه في علم الكلام والفلسفة (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2021)
Ibn Rushd is considered one of the greatest pioneers of enlightenment in the world, and his ideas on adherence to reason had a great influence in the East and the West. Even though, his ideas in the East and West have supporters and opponents, as it is a matter of great ideas. However, Ibn Rushd frequently was misunderstood and his ideas were often carried mistakenly by both of his supporters and opponents. This research is an attempt by the researcher to clarify Ibn Rushd's positions on the issues that raised controversy and discussion among Muslim scholars. The research is also an attempt to recognize his scientific biography and intellectual works. This research included the following topics: Ibn Rushd's biography, his position in theology and his views on philosophy. Keywords: Ibn Rushd, Theology, Philosophy